2017
DOI: 10.1080/00365521.2017.1339828
|View full text |Cite
|
Sign up to set email alerts
|

Is it beneficial to perform surgical resection in elderly patients more than 80 years old with advanced gastric cancer?

Abstract: These results suggest that elderly patients aged 80-85 years with advanced gastric cancer could expect a better prognosis with surgical resection. However, extreme-elderly patients aged ≥86 years should consider the risks and benefits of surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…5,14 In the present study, curative surgery showed significantly better overall survival compared to noncurative treatment and best supportive care despite the more advanced age. This result corresponded to a previous study by Choo et al 2 The better survival outcomes might be from unavoidable selection bias in choosing curative surgery for patients who tend to have a better performance status, relatively higher nutritional status, and the absence of clinical metastasis at the time of the treatment decision. Only four patients in our curative surgery group had a poor performance status, and none of them had severe postoperative complications.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…5,14 In the present study, curative surgery showed significantly better overall survival compared to noncurative treatment and best supportive care despite the more advanced age. This result corresponded to a previous study by Choo et al 2 The better survival outcomes might be from unavoidable selection bias in choosing curative surgery for patients who tend to have a better performance status, relatively higher nutritional status, and the absence of clinical metastasis at the time of the treatment decision. Only four patients in our curative surgery group had a poor performance status, and none of them had severe postoperative complications.…”
Section: Discussionsupporting
confidence: 90%
“…From a recent study in elderly gastric cancer patients over 80 years old, curative resection showed a significant better overall survival compared to supportive care. 2,3 Those who received non-surgical care mostly died from gastric cancer. 3 Cancer-specific survival was 100% in clinical stage I. which can imply that this group died from non-cancer diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study from our hospital compared the survival rates of the surgery group with those of the supportive-care group in elderly patents aged ≥ 80 years with advanced gastric cancer [20]. This study showed that patients aged 80-85 years could expect a better prognosis with surgical resection, and surgical resection in extremely elderly patients aged ≥ 85 years also tended to be associated good prognosis, although there was no statistical significance.…”
Section: Discussionmentioning
confidence: 82%
“…They think that elderly patients should undergo operation because the bene t is the same as for young patients from short-term and long-term prognosis. On the other hand, Choo et al [27] found elderly patients aged 80-85 years could have a large bene t from the surgical resection and for elderly patients aged over 86 years, especially those with cardiovascular and renal system diseases, the risks and bene ts of the procedure should be weighed before surgery. Surgery and chemotherapy should be the recommended treatment strategy in elderly patients which can effectively improve patients' survival compared with conservative treatment [28].…”
Section: Performance In Risk Strati Cation Of Patientsmentioning
confidence: 99%